A Compilation Of Various Research In Manufacturing Engineering Part 1 - Sivarao, Subramonian; Mohd Shukor, Salleh; T. Joseph, Sahaya Anand; Syamimi , Samsudin; Ian Peter, Hasoloan Haery (Penerbit Universiti Teknikal Malaysia Melaka, 2011)
Recent history shows that, many successful final year projects have been developed under the Faculty of Manufacturing Engineering, Universiti Teknikal Malaysia Melaka.